OPPORTUNITIES AND CHALLENGES OF THE IMPLEMENTATION OF ISLAMIC LAW IN INDONESIA - Samsidar Jamaluddin,; Muhrim Djakat,; Hidayatussalam, Hidayatussalam; Sabri Samin,; Misbahuddin, (International Journal of Social Science, 2023)
Islamic law only became an authoritative source (a legal source that has legal force) in constitutional law when the Jakarta Charter was placed in the Republic of Indonesia's Presidential Decree dated 5 July 159 as can be seen in the preamble to the Decree as follows: "That we believe that the Jakarta Charter is dated 22 June 1945 animates the 1945 Constitution and constitutes a series of units in the Constitution.” The word "animating" negatively means that it is not permissible to make laws in the Indonesian state that are contrary to Islamic law for its adherents. Even though Islamic law has failed to be obtained by Islamic parties, the opportunity to make laws based on or inspired by Islamic law through the mechanism of representative democracy in Indonesia is still wide open. Challenges faced by Islamic law The toughest challenge at this time does not lie in the constitutional logic of accommodating Islamic law in national law, but in the dialectics between secular currents of Western thought and expressions of the diversity of Muslims which sometimes creates phobias.